In-the-Moment Profiles of Expectancies, Task Values, and Costs - Dietrich, Julia; Moeller, Julia; Guo, Jiesi; Viljaranta, Jaana; Kracke, Bärbel (Frontiers in Psychology, 2019)
This study focuses on the situational heterogeneity of motivation by investigating in-the-moment profiles of expectancies, task values, and costs within learning situations during a university lecture. In a sample of 155 undergraduate students followed across one semester we examined the occurrence of six hypothesized profiles, situational profile change, and the associations of situational motivation profiles with students’ dispositional motivation. Results of multilevel latent profile analysis revealed three profiles with symmetric levels of expectancies, values, and costs (reflecting high, medium, and low motivation situations), and one profile reflecting motivating but costly situations. Furthermore, situational profiles were associated with students’ motivational dispositions at beginning and end of the semester, and partly related to changes in these dispositions during the semester.